The Effect of Link Income and Sharing Frequency on Brand Attitude in Influencer Marketing: An Exploratory Research on the Differences of Generations X, Y and Z - Kandemir Çomoğlu, Gözde; Huseynli, Bahman; Huseynli, Nigar; Maharramov, Rashad; Samadova, Elnara (International Review of Management and Marketing, 2026)
Customers are now using online channels because of the Covid-19 epidemic and the rise in mobile device use throughout the current era, which has altered their shopping habits. By evolving and employing link income and influencer marketing tactics, businesses have now changed how customers see them. The aim of this research is to examine the effects of link income practices provided by brands to influencers, which affect the perception of the target audience, and the frequency of sponsored content sharing on brand attitudes from the perspective of different generations. Semi-structured focus group interviews, which are exploratory research methods, were preferred due to the research methodology, participants' thoughts, and compatibility with the research process. Within the scope of the research, interviews were conducted with a total of 24 people from Generations X, Y and Z who use social media channels and follow Influencers. As a result of the research, it was determined that excessive sharing frequency has negative consequences. In addition, the influencer categories, content types and features preferred by Generations X, Y and Z cause differences. In this respect, it is thought that the study will provide insight to academics and business owners who will conduct research on this subject.